Pradhan Mantri Matsya Sampada Yojana - A Boon for the Indian Fisheries and Aquaculture Sector - Mohanty, B. P. (Journal of the Inland Fisheries Society of India, 2021)
Fisheries and aquaculture are important for food and nutritional security as well as employment and income generation for a vast population. India being a tropical country with mega biodiversity, fish is both available and affordable. Fish is projected as a 'super-food' owing to its richness in quality animal proteins, heart and brain-friendly omega-3 polyunsaturated fatty acids especially EPA and DHA as well as micronutrients. Fish is a healthy option for hunger and malnutrition alleviation and nutritional security.